Oral and Workshop Abstract Submissions 2015
DOI: 10.1136/bmjspcare-2015-000906.25
|View full text |Cite
|
Sign up to set email alerts
|

OA25 The namaste care programme can enrich quality of life for people with advanced dementia and those who care for them without additional resources

Abstract: Where there was good leadership and adequate clinical care, the Namaste Care programme supported compassionate care and enhanced quality of life for people with advanced dementia at the end of their lives. No additional resources were required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The majority were descriptive accounts of Namaste Care rather than research studies. Of the seven research studies, three included some before-and-after data, 22,44,45 three were qualitative [46][47][48] and one (reported in three papers) 27,29,49 used an action research approach. Only five studies 21,22,27,44,45 presented data on resident outcomes.…”
Section: Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The majority were descriptive accounts of Namaste Care rather than research studies. Of the seven research studies, three included some before-and-after data, 22,44,45 three were qualitative [46][47][48] and one (reported in three papers) 27,29,49 used an action research approach. Only five studies 21,22,27,44,45 presented data on resident outcomes.…”
Section: Phasementioning
confidence: 99%
“…Further details of the Namaste Care studies are listed in additional file 3 of Bunn et al 32 With respect to research design, the 86 papers reported: l 17 evidence reviews (not Namaste Care) [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] l 59 papers reporting 51 primary studies (not Namaste Care) l 10 papers reporting 8 Namaste Care studies. 22,27,29,[44][45][46][47][48]50,130 REALIST REVIEW OF NAMASTE CARE AND OTHER MULTISENSORY INTERVENTIONS NIHR Journals Library www.journalslibrary.nihr.ac.uk…”
Section: Phasementioning
confidence: 99%
“…There is evidence that Namaste Care can increase social interaction, reduce the severity of behavioural and physical symptoms such as agitation [ 8 , 10 , 11 ] and, potentially, lead to cost savings via a reduction in the use of psychotropic medication [ 12 , 13 ]. Qualitative evidence also suggests it can increase family and staff satisfaction with care [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary aim of the program is to improve the quality of life of people with advanced dementia by focusing on a meaningful connection with them, which might result in positive effects in people with dementia and their family caregivers. Studies reported that Namaste Care successfully improves the quality of life of people with advanced dementia and their family caregivers without extra healthcare costs [11][12][13]. Despite the fact that these studies have estimated costs and effects associated with Namaste Care, no full economic evaluation has been performed yet.…”
Section: Introductionmentioning
confidence: 99%